Preparation method and application of MXene-based composite conductive MOF material

By growing Cu-HHTP nanomaterials in situ on the surface of MXene nanosheets, Cu-HHTP/MXene nanocomposites were prepared, and the problem of low response value of Cu-HHTP gas-sensitive materials to triethylamine is solved, and the detection of triethylamine gas with high response value and good selectivity at room temperature is achieved.

CN120082050APending Publication Date: 2025-06-03RES INST OF CHEM DEFENSE PLA ACAD OF MILITARY SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510238405.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

The existing Cu-HHTP gas-sensitive materials have low response values ​​to triethylamine, long response time, and cannot recover from baseline, and poor selectivity.

Method used

Cu-HHTP nanomaterials were grown in situ on the surface of MXene nanosheets by impregnation method to prepare Cu-HHTP/MXene nanocomposites for detection of triethylamine gas.

Benefits of technology

The response value to triethylamine gas was significantly improved at room temperature, and the selectivity and stability were improved, solving the problem of long response time and inability to recover from the baseline.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120082050A_ABST
    Figure CN120082050A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of gas-sensitive sensing materials, and particularly relates to a preparation method and application of an MXene-based composite conductive MOF material. An in-situ formation hydrogen fluoride etching method is adopted to prepare multiple layers of MXene nanosheets easy to disperse, after the multiple layers of MXene nanosheets are changed into a few layers or a single layer through an intercalator and a physical stripping method, Cu metal ions are added for dipping treatment to form tight combination, and then 2, 3, 6, 7, 10, 11-hexahydroxybenzophenanthrene (HHTP) and the multiple layers of MXene nanosheets are mixed and reacted. The synthesized Cu-HHTP / MXene nano composite material has high sensitivity, low detection line, good selectivity and long-term stability to triethylamine gas at room temperature, so that a high-performance triethylamine gas sensor is developed. In addition, the device is simple in process, small in size and suitable for mass production, and has a wide application prospect in the aspect of triethylamine detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sensor materials, and particularly relates to a preparation method and application of an MXene-based composite conductive MOF material. Background Art

[0002] In recent years, with the progress of technology and the times, food safety is related to people's physical health and life safety. It is not only a hot issue of concern to people, but also a top priority for every country. During the spoilage process of food, gas markers such as triethylamine, NH 3 etc. will be produced due to the decomposition of fat, protein, carbohydrates, etc. Therefore, seeking a faster and more convenient method for detecting food freshness is of great significance for ensuring food quality and safety and maintaining human health. At present, most of the gas sensors in mature applications are metal oxide (MOS)-based gas sensors. These sensors are relatively mature in development and have low manufacturing costs. ZnO, SnO 2 etc., and have been widely prepared for triethylamine gas sensing detection. However, the working temperature is usually above 200°C. On the one hand, this will increase the working energy consumption of the sensor, and on the other hand, it may also shorten the service life of the sensor. Moreover, due to the high reactivity of metal oxides with interfering gases at high temperatures, poor selectivity and low stability are often caused.

[0003] At present, the research on single MXene-based gas-sensitive materials generally has problems such as too long response time and inability to recover the baseline. Compared with MOS-based gas-sensitive materials, although there is a great improvement in the working temperature, the response value and response recovery time need to be further doped and modified for improvement. Summary of the Invention

[0004] (1) Technical Problems to be Solved

[0005] The present invention relates to a method for detecting triethylamine gas by a two-dimensional conductive MOF composite MXene material sensor, so as to solve the technical problem of low response value of pure Cu-HHTP gas-sensitive material to triethylamine.

[0006] (2) Technical Solutions

[0007] In order to solve the deficiency of low response value of pure Cu-HHTP gas-sensitive material to triethylamine, the purpose of the present invention is to provide a preparation method of a Cu-HHTP / MXene nano gas-sensitive composite material sensor; the present invention uses an impregnation method to in-situ grow Cu-HHTP nano materials on the surface of MXene nanosheets to prepare Cu-HHTP / MXene nano composite materials, and uses them to detect triethylamine gas; the present invention is used to improve problems such as the inability to recover the response recovery time and poor selectivity of the gas sensor. The material is applied to the gas sensor to achieve selective detection of triethylamine gas at room temperature.

[0008] The technical solution adopted by the present invention is as follows:

[0009] In a first aspect, the present invention provides a method for preparing a two-dimensional conductive MOF composite MXene gas-sensing material. Using lithium fluoride and MAX phase as raw materials and concentrated hydrochloric acid as a solvent, MXene material is prepared by in-situ etching method. Then, an intercalating agent is used to increase the MXene layer spacing, exposing a larger contact area of MXene. Subsequently, copper acetate is dissolved in ethanol and deionized water and added to MXene for ultrasonic treatment. Copper ions enter the MXene interlayer and combine with the functional groups on MXene. Then, a ligand HHTP solution is added, and HHTP further forms a Cu-HHTP / MXene material with copper ions.

[0010] The preparation method specifically includes the following steps:

[0011] S1. Preparation of few-layer MXene: Weigh 1 part by mass of lithium fluoride and dissolve it in hydrochloric acid solution. Add 0.5 - 1.5 parts by mass of Ti 3 AlC 2 to the mixed solution and react fully at 35 - 45 °C. The resulting suspension is washed with deionized water and centrifuged several times until the pH is 5.5 - 6.5. Then, the precipitate is collected and dried to obtain multi-layer MXene. After that, weigh the multi-layer MXene and add an intercalating agent to increase its layer spacing. After rinsing several times with ethanol and deionized water and centrifuging respectively, finally dry to obtain few-layer MXene;

[0012] S2. Preparation of Cu-HHTP / MXene nanocomposite: Weigh the prepared few-layer MXene powder and disperse it into copper acetate Cu 2 (OAc) 4 solution to obtain a Cu 2 (OAc) 4 mixed solution. Pour the Cu 2 (OAc) 4 mixed solution into 2,3,6,7,10,11-hexahydroxybenzo[ghi]perylene HHTP solution to obtain Cu-HHTP / MXene material.

[0013] Preferably, in step S1, the hydrochloric acid is concentrated hydrochloric acid with a concentration of 36 - 38 wt%, and the concentration of lithium fluoride in the concentrated hydrochloric acid is 20 - 100 g / L.

[0014] Preferably, the intercalating agent is dimethyl sulfoxide; the mass ratio of the intercalating agent to the multi-layer MXene is 1:1 - 1:3.

[0015] Preferably, in the step S2, the reaction is carried out in a blast drying oven; the Cu-HHTP / MXene material is washed repeatedly with deionized water and ethanol, and dried in a vacuum drying oven.

[0016] Preferably, in the step S2, the mass ratio of MXene powder to HHTP is 1:2 to 1:5, and the mass ratio of MXene powder to Cu 2 (OAc) 4 is 1:3 to 1:10.

[0017] Preferably, in the step S2, the concentration of the HHTP solution is 1 to 5 g / L, and the Cu 2 (OAc) 4 solution is 3 to 8 g / L.

[0018] In a second aspect, the present invention provides a two-dimensional conductive MOF composite MXene gas-sensitive sensing material prepared by the method described in the first aspect.

[0019] In a third aspect, the present invention provides a method for preparing a gas-sensitive element, which includes: mixing the Cu-HHTP / MXene composite material with deionized water to form a Cu-HHTP / MXene nanostructured gas-sensitive material slurry; brushing the Cu-HHTP / MXene nanostructured heterogeneous gas-sensitive material slurry on an Ag-Pd electrode and drying to obtain a gas-sensitive element.

[0020] In a fourth aspect, the present invention provides an application of a two-dimensional conductive MOF composite MXene nanostructured gas-sensitive material, and the Cu-HHTP / MXene nanostructured gas-sensitive material is applied to the gas sensing detection of triethylamine.

[0021] Furthermore, the Cu-HHTP / MXene nanostructured gas-sensitive material is used to detect triethylamine at room temperature. A fitting curve is prepared by the gas-sensitive response value S = Rg / Ra of the resistance value (Rg) of the material in the standard target gas and the resistance value (Ra) of the material in the air environment to quantitatively detect the position triethylamine.

[0022] (III) Beneficial effects

[0023] The present invention provides a preparation method and application of a Cu-HHTP / MXene nano gas-sensitive composite material sensor. MOF has a large specific surface area and rich porosity, but the presence of the organic framework will lead to poor conductivity of the MOF material, so that the detected gas cannot be better displayed. The introduction of MXene can effectively make up for the problems of chemical instability and low conductivity of MOF. Conversely, the injection of MOF can well solve the serious oxidation degradation and self-aggregation problems of MXene. Due to the carefully designed structure, strong interfacial interaction and sufficient electrochemical properties, the MOF / MXene composite material exhibits better electrochemical properties, active sites and conductive channels than pure MXene and the original MOF. Effectively combining MXene with MOF materials can, on the one hand, increase the specific surface area and modifiability of MXene materials, and on the other hand, improve the conductivity of MOF materials. Therefore, it has great exploration value for the application of related materials in gas-sensing tests.

[0024] The preparation process of the present invention is simple and low-cost. Multilayer MXene is prepared by in-situ etching method, and then the layer spacing is expanded by an intercalating agent. Cu-HHTP / MXene nano-composite material is prepared by metal ion impregnation method. The raw materials are easily obtained and the preparation process is simple, which is suitable for large-scale production. Cu-HHTP nano-materials are grown on the surface of MXene nanosheets to form a unique spatial structure and increase the specific surface area of the material, which can effectively promote gas adsorption and electron transfer, and strengthen the gas-sensing performance of the material. The nano-composite material can exhibit high response, good selectivity and long-term stability to triethylamine gas at room temperature. The Cu-HHTP / MXene-based triethylamine gas sensor prepared by the present invention has a simple device process and a small volume, and is suitable for industrial mass production. Brief Description of the Drawings

[0025] Figure 1 XRD spectra of MXene, Cu-HHTP(alcohol), Cu-HHTP(water), Cu-HHTP / MXene(water) and Cu-HHTP / MXene(alcohol);

[0026] Figure 2 (a-b) Scanning electron microscope pictures of the product prepared in Example 1 of MXene;

[0027] Figure 3 (a-b) Transmission electron microscope pictures of the product prepared in Example 1 of MXene;

[0028] Figure 4 (a) Scanning electron microscope picture of the product prepared in Example 2 of Cu-HHTP(water);

[0029] Figure 4(b) Scanning electron microscope image of the product prepared in Example 3 of Cu-HHTP(alcohol);

[0030] Figure 4 (c) Scanning electron microscope image of the product prepared in Example 4 of Cu-HHTP / MXene(water);

[0031] Figure 4 (d) Scanning electron microscope image of the product prepared in Example 5 of Cu-HHTP / MXene(alcohol);

[0032] Figure 5 Transmission electron microscope image of the product prepared in Example 5 of Cu-HHTP / MXene(alcohol);

[0033] Figure 6 Gas-sensing detection diagram of the Cu-HHTP(alcohol) gas sensor for triethylamine at room temperature.

[0034] Figure 7 Gas-sensing detection diagram of the Cu-HHTP / MXene(alcohol) gas sensor for triethylamine at room temperature. Specific implementation manners

[0035] To make the objectives, contents and advantages of the present invention clearer, the following further describes in detail the specific implementation manners of the present invention with reference to the drawings and embodiments.

[0036] Example 1

[0037] Preparation method of few-layer MXene material:

[0038] S1. Conduct the experiment in a fume hood. Put 1.0 g of lithium fluoride into a beaker made of polytetrafluoroethylene, then add it to 20 ml of 9M hydrochloric acid and stir magnetically at 600 rpm for 10 minutes.

[0039] S2. After the above solution is dissolved and mixed evenly, slowly add 1.0 g of Ti 3 AlC 2 in multiple times, and then heat and stir in a constant-temperature water bath at 40 °C for 24 hours. Subsequently, pour the solution into a centrifuge tube and centrifuge at 8000 rpm for 5 minutes.

[0040] S3. Wash it 2-3 times with 2M dilute hydrochloric acid, then wash it with deionized water (DI) until the pH of the supernatant is 6, repeat this process 8 times, and then collect the precipitate and dry it in a vacuum drying oven for 12 hours to obtain multi-layer MXene.

[0041] S4. Then weigh 10 mg of multi-layer MXene, put it into a beaker, and add 5 ml of dimethyl sulfoxide, and ultrasonicate it in an ice bath for 1 hour.

[0042] S5. Then, stir magnetically at room temperature for 17 hours, and centrifuge with ethanol and water three times each. Finally, dry in a vacuum drying oven for 12 hours to obtain few-layer MXene.

[0043] Example 2

[0044] Preparation of Cu-HHTP / MXene (aqueous) nanocomposite.

[0045] Weigh 10 mg of the few-layer MXene powder prepared in Example 1 and disperse it into 10 mL of a 5 g·L -1 Cu 2 (OAc) 4 solution with deionized water as the solvent. Under ultrasonic conditions, quickly pour 10 mL of the Cu 2 (OAc) 4 mixed solution into a 35 mg HHTP solution dissolved in 25 mL of deionized water. The solution turns black, and then ultrasonic for 15 minutes;

[0046] S2. React at 85 °C for 12 h in a forced-air drying oven. Wash the Cu-HHTP / MXene (aqueous) material with deionized water and ethanol repeatedly three times, and dry in vacuum at 60 °C for 24 h.

[0047] Example 3

[0048] Preparation of Cu-HHTP / MXene (alcoholic) nanocomposite.

[0049] Weigh 10 mg of the few-layer MXene powder prepared in Example 1 and disperse it into a 5 g·L -1 Cu 2 (OAc) 4 solution with absolute ethanol as the solvent. Subsequently, the preparation is the same as that in Example 2.

[0050] Comparative Example 1

[0051] Preparation method of Cu-HHTP (aqueous) nanomaterial.

[0052] S1. Prepare a 5 g·L -1 Cu 2 (OAc) 4 solution with deionized water as the solvent. Under ultrasonic conditions, quickly pour 10 mL of the Cu 2 (OAc) 4 mixed solution into a 35 mg HHTP solution dissolved in 10 mL of deionized water. The solution turns black, and then ultrasonic for 15 minutes;

[0053] S2. React at 85 °C for 12 h in a forced-air drying oven. Wash the Cu-HHTP (aqueous) material with deionized water and ethanol repeatedly three times, and dry in vacuum at 60 °C for 24 h.

[0054] Comparative Example 2

[0055] Preparation of Cu-HHTP(alcohol) nanomaterials.

[0056] Only the solvent was changed, deionized water was replaced with absolute ethanol, and the reaction temperature was 45 °C.

[0057] Test effect

[0058] The manufacturing process of the gas sensor is as follows:

[0059] S1. Weigh 5 mg of the composite gas-sensitive material in an agate mortar, add 1 mL of absolute ethanol, and grind it into a slurry with appropriate strength.

[0060] S2. Brush the slurry onto a cleaned Ag-Pd electrode (14 mm × 7 mm) and let it dry naturally at room temperature to obtain a gas sensor.

[0061] The specific calculation method of sensitivity is to use the resistance value (R g ) of the material in the target gas and the resistance value (R a ) of the material in the air environment, and define the gas-sensitive response value as S = (R g / R a ).

[0062] The XRD diffraction patterns of the materials such as MXene, Cu-HHTP(alcohol), Cu-HHTP(water), Cu-HHTP / MXene(water), and Cu-HHTP / MXene(alcohol) obtained in Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2 are shown in Figure 1 . As shown in the figure, the diffraction peaks at 6.3° and 61.7° coincide with the XRD pattern of MXene reported in the literature, corresponding to the (002) and (110) crystal planes respectively; while the peaks at 9.4°, 12.3°, and 27.9° are consistent with the (200), (210), and (001) crystal planes of Cu-HHTP reported in the literature, and Cu-HHTP / MXene corresponds to the above peak crystal planes. It is proved that the present invention has successfully synthesized single MXene, Cu-HHTP(alcohol), and Cu-HHTP(water), as well as the composite materials Cu-HHTP / MXene(water) and Cu-HHTP / MXene(alcohol).

[0063] From the obtained SEM( Figure 2 a) and SEM( Figure 2 b), it can be seen that the MXene material has a classic accordion-like layered structure and has a relatively large gap. TEM( Figure 3In (a-b), it can be seen that Ti3AlC2 is fully etched to obtain few-layer MXene, and obvious layered structures can be seen from the edges.

[0064] Figure 4 (a) The scanning image of Cu-HHTP (water) shows the columnar structure of the material. Figure 4 (b) The scanning image of Cu-HHTP (alcohol) shows that the surface is granular and adhered together. Figure 4 (c) The scanning image of Cu-HHTP / MXene (water) shows that under the influence of MXene, the crystal size increases and the columnar diameter becomes thicker. Figure 4 (d) The scanning image of Cu-HHTP / MXene (alcohol) shows that the adhered nanoparticle Cu-HHTP tightly wraps the MXene material, forming a tight combination.

[0065] Figure 5 The transmission image of Cu-HHTP / MXene (alcohol) is shown, and it can be observed Figure 5 (a) There are whisker-like crystal materials around the material, indicating that Cu-HHTP grows around the MXene material. Figure 5 (b) By calculation, it can be obtained that the longitudinal lattice fringe is the lattice spacing d≈0.261nm of MXene corresponding to the crystal plane (008), and the transverse lattice fringe is the lattice spacing d≈0.332nm of Cu-HHTP corresponding to the crystal plane (001).

[0066] This shows the response of the gas sensor obtained in Example 3 to triethylamine at room temperature. Since the test results of triethylamine in Example 2 could not be restored, Example 3 was mainly used to detect triethylamine gas. Figure 6 (a) The graph of the response resistance relationship of the composite material Cu-HHTP (alcohol) to triethylamine gas at different concentrations. Figure 6 (b) The restored response value shows that as the concentration of triethylamine gas increases, the response value also increases. Plotting Figure 6 (c) The linear correlation graph gives R2 = 0.958. Subsequently, the response of this material to 10 ppm triethylamine gas ( Figure 6 d) is 1.048, and the response recovery times are 35 s / 39 s respectively.

[0067] Figure 7 This shows the response of the composite material Cu-HHTP / MXene (alcohol) prepared in Example 5 to triethylamine at room temperature. Since the test results of triethylamine in Example 4 could not be restored either, Example 5 was mainly used to detect triethylamine gas. Figure 7(a) Relationship diagram of the response resistance of the composite material Cu-HHTP / MXene(alcohol) to triethylamine gas at different concentrations. The successful introduction of MXene effectively reduces its resistance by about half, enhances electron transport, and effectively improves the gas-sensing characteristics. Figure 7 (b) To restore the response value, it can be observed that as the concentration of triethylamine gas increases, the response value also increases, which is much higher than that of pure Cu-HHTP(alcohol). Plot Figure 7 (c) The linear correlation diagram gives R2 = 0.978, which has a higher linear correlation compared to Cu-HHTP(alcohol). Figure 7 (d) The response value of Cu-HHTP / MXene(alcohol) to 10 ppm triethylamine gas is 1.115, and the response and recovery times are 36 s / 42 s respectively.

[0068] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the technical principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a two-dimensional conductive MOF composite MXene gas sensitive sensing material, characterized in that: The preparation method specifically comprises the following steps: S1. Preparation of few-layer MXene: Weigh 1 part by mass of lithium fluoride and dissolve it in a hydrochloric acid solution, add 0.5-1.5 parts by mass of Ti3AlC2 to the mixed solution, and fully react at 35-45°C; wash the resulting suspension with deionized water and centrifuge it several times until the pH is 5.5-6.5, then collect the precipitate to obtain multilayer MXene; then weigh the multilayer MXene and add the intercalation agent to obtain a few-layer MXene; S2. Preparation of Cu-HHTP / MXene nanocomposite materials: Weigh the prepared few-layer MXene and disperse it into copper acetate Cu2(OAc)4 solution to obtain a Cu2(OAc)4 mixed solution; pour the Cu2(OAc)4 mixed solution into 2,3,6,7,10,11-hexahydroxytriphenylene HHTP solution to obtain Cu-HHTP / MXene material.

2. The method for preparing a two-dimensional conductive MOF composite MXene gas sensitive sensing material according to claim 1, characterized in that: In the step S1, the hydrochloric acid is 36-38 wt % concentrated hydrochloric acid, and the concentration of lithium fluoride in the concentrated hydrochloric acid is 20-100 g / L.

3. The method for preparing a two-dimensional conductive MOF composite MXene gas sensitive sensing material according to claim 1, characterized in that: The intercalant is dimethyl sulfoxide; the mass ratio of the intercalant to the multilayer MXene is 1:1 to 1:

3.

4. The method for preparing a two-dimensional conductive MOF composite MXene gas sensitive sensing material according to claim 1, characterized in that: In the step S2, the reaction is carried out in a forced air drying oven; the Cu-HHTP / MXene material sample is repeatedly washed with deionized water and ethanol, and then dried in a vacuum drying oven.

5. The method for preparing a two-dimensional conductive MOF composite MXene gas sensitive sensing material according to claim 1, characterized in that: In the step S2, the mass ratio of MXene powder to HHTP is 1:2 to 1:5, and the mass ratio of MXene powder to Cu2(OAc)4 is 1:3 to 1:

10.

6. The method for preparing a two-dimensional conductive MOF composite MXene gas sensitive sensing material according to claim 1, characterized in that: In step S2, the concentration of the HHTP solution is 1-5 g / L, and the concentration of the Cu2(OAc)4 solution is 3-8 g / L.

7. A two-dimensional conductive MOF composite MXene gas sensitive sensing material prepared by the method described in any one of claims 1 to 6.

8. A method for preparing a gas sensor, the method comprising: The Cu-HHTP / MXene composite material is mixed with deionized water to form a Cu-HHTP / MXene nanostructured gas-sensitive material slurry; the Cu-HHTP / MXene nanoheterostructured gas-sensitive material slurry is applied on an Ag-Pd electrode and dried to obtain a gas-sensitive element.

9. Use of the gas sensitive element according to claim 8 for triethylamine gas sensing detection.

10. The use of the gas sensor according to claim 9 for triethylamine gas sensing detection, characterized in that: The Cu-HHTP / MXene nanostructured gas-sensitive material is used at room temperature to prepare a fitting curve by using the gas-sensitive response value S=Rg / Ra of the material in the standard target gas triethylamine (Rg) and the resistance value of the material in the air environment (Ra), and the unknown concentration of triethylamine is quantitatively detected.

Citation Information

Cited By

  • Bimetal conductive MOF-based gas sensitive material, preparation method and semiconductor sensor

    CN121453859A